Conservative Management Of Placenta Accreta: A Case Report - Murga-Lopez, Agustín (2019)
The aim of this paper is to present the first reported case in the INMP of placenta accreta managed conservatively and a critical review of the literature. The placenta accreta is a condition that involves a significant morbidity from obstetric view, which traditionally has been managed with hysterectomy. However, in recent years increasingly more cases reported conservative management, with encouraging results from the viewpoint of reproduction.